Preparation and characterization of acrylic acid-grafted-carboxymethyl sago starch for removal of Cadmium(ii) and Chromium(iii) from aqueaus solution - Kamarudin, Sabariah (2013)
Polysaccharides such as starch and cellulose play important role in the polymer research because they are from natural resources and biodegradable. Their use in non-food applications depends on unique special properties they provide, often at costs below those of synthetic polymer. Chemically modified starches with improved properties are gaining increasing importance in industry not only because they are low in cost, but mainly because the polysaccharide portion of the product is biodegradable. In this study, carboxymethyl sago starch (CMSS) was grafted with acrylic acid monomer by radical polymerization technique, using electron beam irradiation. Effect of monomer absorption, degree of substitution (OS) of CMSS, radiation condition and irradiation dose during irradiation grafting process were investigated. Percentage of grafting was determined by thermogravimetry method using thermal gravimetic analysis (TGA). Thermogram of the combustion shows 3 steps of decomposition. Study showed that optimum grafting was 121.7% was achieved for CMSS with OS 1.0, 15 kGy irradiation doses. The grafted CMSS was characterized using TGA, Fourier transformed infrared spectroscopy (FTIR) and scanning electron micrography (SEM). The swelling of grafted CMSS is up to 7927% for grafted CMSS OS 1.0 and 4869% for grafted CMSS OS 1.2. Grafted CMSS was then applied for removal of Cr(lll), and Cd(lI) ions from aqueous solution by using adsorption method. Analysis of the metal adsorption was quantified using inductively coupled plasma optical emission spectroscopy (ICP-OES). The influences of various parameters such as degree of substitution of CMSS, pH and adsorption temperature were investigated. Cadmium was the highest adsorbed metal on grafted CMSS with maximum percentage of adsorption 97% while for chromium, the maximum percentage of adsorption was 48% using grafted CMSS OS 1.0. Results showed that grafted CMSS OS 1.0 gave higher adsorption of metal ion compare to grafted CMSS OS 1.2. The results showed that carboxymethyl sago starch grafted acrylic acid could be an effective and economical adsorbent for removal of heavy metals ions from industrial wastewater.